DegP primarily functions as a protease for the biogenesis of β‐barrel outer membrane proteins in the Gram‐negative bacterium Escherichia coli. (15th January 2014) - Ge, Xi; Wang, Rui; Ma, Jing; Liu, Yang; Ezemaduka, Anastasia N.; Chen, Peng R.; Fu, Xinmiao; Chang, Zengyi
<x xml:space="preserve">Abstract</x> DegP (also designated as HtrA) and its homologs are found in prokaryotic cells and such eukaryotic organelles as mitochondria and chloroplasts. DegP has been found to be essential for the growth of Gram‐negative bacteria under heat shock conditions and arguably considered to possess both protease and chaperone activities. The function of DegP has not been clearly defined. Using genetically incorporated non‐natural amino acids as photo‐crosslinkers, here we identified the β‐barrel outer membrane proteins (OMPs) as the major natural substrates of DegP in Escherichia coli cells. We also demonstrated that DegP primarily functions as a protease, at both low and high temperatures, to eliminate unfolded OMPs, with hardly any appreciable chaperone activity in cells. We also found that the toxic and cell membrane‐damaging misfolded OMPs would accumulate in DegP‐lacking cells cultured under heat shock conditions. Together, our study defines the primary function of DegP in OMP biogenesis and offers a mechanistic insight into the essentiality of DegP for cell growth under heat shock conditions. Structured digital abstract DegP physically interacts with ompA by pull down (1, 2) DegP physically interacts with ompX, ompA, ompW, ompF, nmpC and ompC by pull down (View interaction) DegP physically interacts with ompC and ompF by pull down (View interaction) DegP physically interacts with ompC and ompA by pull down (View interaction) DegP physically interacts with ompC, malE, fkpA, ompW, ompA, ompF, nmpC and ompX by cross-linking study (View interaction)